Advanced Clinical Neonatal Nursing Students’ Transfer of Performance: From Skills Training With Real-Time Feedback on Ventilation to a Simulated Neonatal Resuscitation Scenario - Rød, Irene; Jørstad, Anna-Kristi; Aagaard, Hanne; Rønnestad, Arild; Solevåg, Anne Lee (Frontiers in Pediatrics, 2022)
Background Advanced clinical neonatal nurses are expected to have technical skills including bag-mask ventilation. Previous studies on neonatal bag-mask ventilation skills training focus largely on medical students and/or physicians. The aim of this study was to investigate whether advanced clinical neonatal nursing students’ bag-mask ventilation training with real-time feedback resulted in transfer of bag-mask ventilation performance to a simulated setting without feedback on ventilation. Materials and Methods Students in advanced clinical neonatal nursing practiced bag-mask ventilation on a premature manikin (Premature Anne, Laerdal Medical, Stavanger, Norway) during skills training. A flow sensor (Neo Training, Monivent AB, Gothenburg, Sweden) was placed between the facemask and the self-inflating bag (Laerdal Medical), and visual feedback on mask leak (%), expiratory tidal volume (VTe in ml/kg), ventilation rate and inflation pressure was provided. Two months later, the students participated in a simulated neonatal resuscitation scenario. The same variables were recorded, but not fed back to the students. We compared ventilation data from skills- and simulation training. A structured questionnaire was used to investigate the students’ self-perceived neonatal ventilation competence before and after the skills- and simulation training. Results Mask leakage and ventilation rate was higher, and VTe lower and highly variable in the simulated scenario compared with skills training (all p<0.001). There was no statistically significant difference in inflation pressure (p=0.92). The fraction of ventilations with VTe within the target range was lower during simulation (21%) compared to skills training (30%) (p<0.001). There was no difference in the students’ self-perceived competence in bag-mask ventilation before vs. after skills- and simulation training. Conclusion Skills training with real-time feedback on mask leak, ventilation rate, tidal volume and inflation pressure did not result in objective or subjective improvements in bag-mask ventilation in a simulated neonatal resuscitation situation. Incorrect VTe delivery was common even when feedback was provided. It would be of interest to study whether more frequent training, and training both with and without feedback, could improve transfer of performance to a simulated resuscitation setting.